a=2x b=3 (2x+3)²=(2x)²+2·2x·3+3²=4x²+12x+9 3) x²y²-9 формула a²-b²=(a-b)(a+b) a=xy b=3 x²y²-9=(xy)²-3²=(xy-3)(xy+3)
4) 9/16+b²-9/8b формула a²-2ab+b²=(a-b)² a²=9/16 ⇒ a=3/4 b²=b² ⇒ b=b 2ab=2·(3/4)·b=6/4b≠9/8b не является формулой 5) x²+12x+36 формула a²+2ab+b²=(a+b)²
a=2x b=3 (2x+3)²=(2x)²+2·2x·3+3²=4x²+12x+9 3) x²y²-9 формула a²-b²=(a-b)(a+b) a=xy b=3 x²y²-9=(xy)²-3²=(xy-3)(xy+3)
4) 9/16+b²-9/8b формула a²-2ab+b²=(a-b)² a²=9/16 ⇒ a=3/4 b²=b² ⇒ b=b 2ab=2·(3/4)·b=6/4b≠9/8b не является формулой 5) x²+12x+36 формула a²+2ab+b²=(a+b)²